(3GdJfXje hGdEOGQI (B:s (3eONd eYGUQ dYedjGJ GdJNWjW hGdJfXje hGdbjGOI hGdQbGHI (B/s - (3GdeUQj, SYjO eMeOs ((3GdEScfOQjI(B: s (3GdOGQ GdLGeYjI(B, s, 2002)
(3JWhQ GdacQ GdGOGQj ,eQGMd JWhQ GdacQ GdGOGQj,HYV GdeaGgje GdMOjKI aj GdGOGQI (B-(3YedjI GdJNWjW hGJNGP GdbQGQGJ,YedjI GdJNWjW ,GJNGP GdbQGQGJ(B-(3GdJfXje ,GdOQGSGJ GdJfXjejI hfXQjI GdfXe ,eaghe GdJQGcejI GdJfXjejI,eaGgje CSGSjI aj GdJfXje,GdYedjdJ GdbjGOjI ,GdeOGNd dOQGSI GdbjGOI,CfeGW GdbjGOI ,fLGM haYGdjI GdbjGOI(B-(3GdQbGHI ,GfhGYgG heQGMdgG hYfGUQgG ,hSGFd GdQbGHI hJcfhdhLjG GdeYdheGJs
(3GdeQGLY U(B.342s
Keywords: (3GdEOGQIs; (3GdJNWjW h GdbjGOIs; (3GdJfXjes; (3GdQbGHIs